Association between cachexia, chemotherapy and outcomes in older cancer patients: A systematic review. Issue 6 (December 2017) - Caillet, Philippe; Liuu, Evelyne; Raynaud Simon, Agathe; Bonnefoy, Marc; Guerin, Olivier; Berrut, Gilles; Lesourd, Bruno; Jeandel, Claude; Ferry, Monique; Rolland, Yves; Paillaud, Elena
Summary: Background & aims: The aims of this systematic review were (i) to determine the prevalence of malnutrition and cachexia in older cancer patients in a chemotherapy setting, and (ii) to report the chemotherapy-related causes of malnutrition and (iii) the consequences of malnutrition on the outcomes of these patients. Methods: We searched MEDLINE for articles published in English or French between 2005 and 2016 and which reported retrospective or prospective, observational or interventional studies of the prevalence of malnutrition and its consequences in patients 65 years or older with solid tumors and chemotherapy-related causes of malnutrition. Results and conclusion: Malnutrition is prevalent up to 83% in older patients with cancer scheduled to receive chemotherapy. One third or more of patients were malnourished before receiving chemotherapy. A weight loss of 10% or more during the past three or six months was reported in 8%–40% of cancer patients, while a body mass index <21 kg/m 2 was found in 10.7%–23%. Malnutrition was more prevalent in digestive (28%–75%) than in non-digestive cancers (8%–46.9%), and also in metastatic cancers (64%–76.5%). During the course of chemotherapy, weight loss was observed in 40%–91.6% of patients, depending on cancer location. The most frequently reported chemotherapy-related digestive symptoms likely to impair nutritional status were dry mouth, nausea, stomach pain, diarrhea and constipation. Low Mini-Nutritional-Assessment score was an independent predictor of early discontinuation of chemotherapy and increased the risk of mortality.